Ion deposition bias to suppress dendrite formation and growth in metal-ion battery cells
By introducing porous structures and deposition biasing elements into the lithium metal anode, the problems of dendrites' growth and volume changes are solved, and the high life and energy density of the lithium-ion battery pack are achieved.
Patent Information
- Application Number
- CN201980017371.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2018-03-05
- Filing Date
- 2019-02-20
- Publication Date
- 2024-12-24
- Estimated Expiration
- 2039-02-20
AI Technical Summary
The existing lithium metal anodes are prone to form an uneven dendrite structure during charging, resulting in a short life of the battery pack and large volume changes. Under the conditions of fast charging, mechanical rigid electrolytes cannot effectively inhibit dendrite growth, resulting in a decline in battery performance.
Using a porous structure of lithium-based ceramic material as an anode, combining the deposition biasing elements such as seed layer and dendritic quenching layer, the lithium ions tend to be biased towards the current collector during charging, avoiding the Uneven deposition inhibits dendrites and further controls ion deposition through an electronically conductive coating.
Effectively inhibit the formation and growth of dendrites, improve the life of multiple charge and discharge cycles of the battery pack, reduce volume changes during the charge and discharge process, and ensure uniform operation of the battery pack and high energy density.
Smart Images

Figure CN111788718B_ABST
Abstract
Description
[0001] Related Applications
[0002] This application claims priority to U.S. Provisional Patent Application No. 62 / 638,597, filed on March 5, 2018, entitled “SOLID STATELITHIUM METAL DIMENSIONALLY STABLE ANODE,” the entire contents of which are incorporated herein in their entirety. Technical Field
[0003] The present disclosure relates generally to battery components and, more particularly, to anodes for metal ion battery cells.
[0004] background
[0005] Unless otherwise indicated herein, the materials described in this section are not prior art to the claims in this application and are not admitted to be prior art by inclusion in this section.
[0006] Several qualities of Li metal have prompted efforts to incorporate Li metal-based components into batteries. Li metal has a theoretical capacity of 3860 mAh / g, thus providing the highest capacity of any known anode material for Li-ion batteries. Therefore, batteries containing lithium metal or lithium alloy anodes can have higher specific energies than batteries containing anodes formed from other materials. For example, lithium / sulfur and lithium / air batteries have the potential to reach specific energies of 500 to 1000 Wh / kg or more. However, these desirable qualities have some drawbacks that prevent Li metal from being used as anodes in batteries.
[0007] In particular, batteries with Li metal anodes typically have a limited lifespan due to the formation of electronically conductive dendrite structures. During charging, Li ions move from the cathode to the anode, and vice versa during discharge. Over successive charge / discharge cycles, the Li ions have a tendency to accumulate in needle- or moss-like structures (i.e., "dendrites") rather than being uniformly deposited. Dendrites can form for a variety of reasons, including discontinuities in the anode surface, impurities within the anode, and properties within the anode such as current density (mA / cm 2 ) during the charging process. Li ions accumulate into dendrites over continuous cycling, thereby extracting Li metal material from the anode and can cause parasitic capacity loss in the battery. Furthermore, in the worst case, the dendrites can continue to grow and form a short circuit between the anode and cathode of the battery. Short circuits between battery electrodes can severely reduce the life of the battery and can be dangerous.
[0008] In an effort to suppress dendrite growth, batteries with Li metal anodes typically contain mechanically rigid electrolytes such as solid polymer materials, composite oxides, glasses, and other compounds. Such materials can act as mechanical boundaries that physically constrain dendrite growth. However, in the presence of elevated current densities, such as current densities > 1 mA / cm 2 In the case of a mechanically rigid electrolyte, the ability to act as a mechanical boundary is generally reduced. At faster charge rates, the current density increases, and thus such materials cannot effectively act as dendrite growth inhibitors for battery applications requiring fast charging.
[0009] Additional drawbacks of introducing Li metal anodes include (i) the tendency of Li metal to accumulate on surface defects of solid components, which can lead to accelerated failure modes in the presence of defects in the separator between the anode and cathode, (ii) generally unrestricted Li metal growth during Li ion deposition during charging, which leads to inhomogeneities within the anode and reduced cell performance, and (iii) volume changes of the Li metal anode during charge and discharge of the battery, which can affect the lifetime and structural integrity of the battery.
[0010] Therefore, battery assemblies that have high lifespan and inhibit dendrite growth are beneficial. Battery assemblies that operate uniformly during charge and discharge are also beneficial. Battery assemblies that have limited or no volume change during charge and discharge are also beneficial.
[0011] Overview
[0012] To inhibit dendrite growth and / or formation, a battery cell includes a first current collector, a separator, an anode, and at least one deposition biasing element. The anode is disposed between the first current collector and the separator and comprises an ion conductive material having a porous structure. The at least one deposition biasing element is disposed within the battery cell to deflect ion deposition within the anode away from the separator during charging of the battery cell.
[0013] In some embodiments, the ion conductive material is a Li-based ceramic material.
[0014] In some embodiments, the at least one deposition biasing element includes a seed layer. The seed layer has a discrete concentration of a metal material corresponding to the ions conducted by the ion conductive material. The seed layer is disposed between the first current collector and the separator to be closer to the first current collector than to the separator, and is configured to bias ion deposition in the anode toward the first current collector.
[0015] In some embodiments, the battery cell is configured so that in a fully discharged state, about 20 weight percent of the total amount of metallic material corresponding to ions conducted by the ionically conductive material remains within the seed layer.
[0016] In some embodiments, the at least one deposition biasing element includes a dendrite quenching layer. The dendrite quenching layer has a material configured to form an alloy with a metal material corresponding to ions conducted by the ion conductive material. The dendrite quenching layer is disposed in an interface region between the anode and the diaphragm and is configured to deflect ion deposition in the anode away from the diaphragm.
[0017] In some embodiments, the at least one deposition biasing element comprises an electronically conductive coating applied to a portion of the anode porous structure adjacent to the first current collector. The electronically conductive coating is configured to bias ion deposition within the anode toward the first current collector and away from the separator.
[0018] In some embodiments, the anode includes a substrate formed from fibers of a polymeric material. In some embodiments, the ionically conductive material is a coating applied to the fibers of the polymeric material to form a porous structure.
[0019] In some embodiments, the anode has a porosity of about 60% to about 90%.
[0020] To inhibit dendrite growth and / or formation, a method of forming a battery cell includes electrospinning material particles into a web to form an anode, the anode including an ionically conductive material. At least one deposition biasing element is applied to at least one of the anode and a first current collector. The anode is disposed between the first current collector and the separator so that the first current collector forms a first interface with a first side of the anode and a second interface with the separator. The first current collector and the separator are joined to the anode.
[0021] In some embodiments, applying the at least one deposition biasing element includes applying a seed layer between the first current collector and the separator to be closer to the first current collector than to the separator. The seed layer comprises a discrete concentration of a metal material corresponding to the ions conducted by the ion conductive material and is configured to bias ion deposition within the anode toward the first current collector during charging.
[0022] In some embodiments, applying the at least one deposition biasing element includes applying a dendrite quenching layer to the second face of the anode. The dendrite quenching layer has a material configured to form an alloy with a metal material corresponding to ions conducted by the ion conductive material. The dendrite quenching layer is configured to bias ion deposition within the anode away from the separator during charging.
[0023] In some embodiments, applying the at least one deposition biasing element comprises applying a coating of an electronically conductive material to a portion of the anode adjacent the first face. The remainder of the anode is purely ionically conductive to bias ion deposition within the anode toward the first current collector and away from the separator during charging.
[0024] In some embodiments, the method further includes bonding a cathode and a second current collector to a side of the separator opposite the anode to position the cathode between the separator and the second current collector.
[0025] In some embodiments, the anode, separator, and cathode are solid state, such that the battery cell is a solid state battery cell.
[0026] In some embodiments, the ion conductive material is a Li-based ceramic material. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] Figure 1 An exemplary embodiment of a battery cell according to the present disclosure is depicted.
[0029] Figure 2a Another exemplary embodiment of a battery cell according to the present disclosure is depicted.
[0030] Figure 2b Describes the Figure 2a A charging system for charging the battery pack batteries.
[0031] Figure 3 Another exemplary embodiment of a battery cell according to the present disclosure is depicted.
[0032] Figure 4 One exemplary method for forming an anode for a battery cell according to the present disclosure is depicted.
[0033] Figure 5 Another exemplary method for forming an anode for a battery cell according to the present disclosure is depicted.
[0034] Figure 6 One exemplary method for forming a battery cell according to the present disclosure is depicted.
[0035] Details
[0036] In order to facilitate an understanding of the principles of the present disclosure, reference is now made to the accompanying drawings and the description in the following written specification. This reference is not intended to limit the scope of the subject matter. The present disclosure also includes any changes and modifications to the illustrated embodiments and includes further applications of the principles of the embodiments as would normally occur to a person skilled in the art.
[0037] Techniques for inhibiting dendrite formation and growth within a battery cell are introduced herein. During charging of the battery cell, a deposition biasing element biases Li ion deposition toward the current collector and / or away from the interface between the anode and the separator. Such biasing inhibits dendrite formation and growth within the anode and improves the life of the battery cell over multiple charge / discharge cycles.
[0038] Also introduced herein is a technique for reducing the volume change of the battery pack during charging and discharging and promoting uniform operation of the battery pack components. In various embodiments, the anode has a porous skeleton structure. During charging, Li ions are deposited in the porous structure, rather than only on the anode surface at the interface between the anode and the separator. Such deposition causes the Li ions to be more evenly distributed in the anode during charging, reducing the volume change experienced by the anode and increasing the effective surface area of the anode.
[0039] Figure 1 An exemplary embodiment of a metal ion metal battery cell 100 according to the present disclosure is depicted. In some embodiments, the battery cell 100 is a Li-ion battery cell. The battery cell 100 includes a first current collector 102, an anode 104, a separator 106, a cathode 108, a second current collector 110, and a deposition bias element 112. The separator 106 is disposed between the anode 104 and the cathode 108. The anode 104 is disposed between the first current collector 102 and the separator 106. The cathode 108 is disposed between the separator 106 and the second current collector 110. In some embodiments, the deposition bias element 112 is disposed between the first current collector 102 and the separator 106 to be closer to the first current collector 102 than the separator 106. In some embodiments, the deposition bias element 112 is disposed at a first interface 114 between the first current collector 102 and the anode 104.
[0040] As used herein, "charging process" refers to the process of storing electrical energy in a battery cell. For example, when a positive voltage is applied between the second current collector 110 and the first current collector 102 of the battery cell 100, metal ions migrate from the cathode 108 through the separator 106 and are deposited in the anode 104. The metal ions stored in the anode 104 are equivalent to the energy storage capacity of the battery cell 100.
[0041] As used herein, "discharge process" refers to the process of extracting stored electrical energy from a battery cell. For example, when a load is connected between the first current collector 102 and the second current collector 110 of the battery cell 100, metal ions migrate from the anode 104 through the separator 106 and are deposited in the cathode 108. The release of metal ions from the anode 104 forms a free electron flow that is collected by the first current collector 102, which results in a positive current from the second current collector 110 through the load to the first current collector 102.
[0042] The first current collector 102 is a substrate comprising any acceptable conductive material, such as copper, nickel, steel, or titanium. In some embodiments, the first current collector 102 is a sheet, but in other embodiments other types of current collectors are used, such as meshes, plates, etc. In some embodiments, the first current collector 102 is a monopolar current collector. In some embodiments, the first current collector 102 is a bipolar current collector, that is, the surface of the first current collector 102 facing away from the anode 104 is the second current collector of another battery cell.
[0043] Anode 104 is a solid metal-based anode having a porous structure 116. It should be understood that "porous" as used herein refers to the void fraction of the anode material (e.g., the voids between regions of the material), rather than the volume of such a material that receives ions (e.g., the voids between molecules of the material). Porous structure 116 acts as a host for deposition of metal ions during charging of battery cell 100. Specifically, porous structure 116 increases the effective surface area of anode 104.
[0044] In other words, the inner surface of the porous structure 116 is exposed to the metal ions received by the anode 104 from the separator 106, rather than only the surface of the anode 104 at the second interface 118 between the anode 104 and the separator 106. Therefore, the deposition of metal ions is more uniformly distributed throughout the anode 104 compared to conventional anodes. The more uniform distribution of metal ion deposition within the anode results in a more uniform current density within the anode and can have an inhibitory effect on dendrite formation and growth.
[0045] In addition, due to the porous structure 116, the current in the anode 104 is distributed over a larger surface area during charging. Therefore, the magnitude of the current density in the anode 104 is reduced compared to conventional anodes, thereby being able to increase the charge rate of the battery cell 100. In addition, since the metal ions are deposited in the porous structure 116 of the anode 104 rather than only at the second interface 118, the deposited metal ions tend to fill the porous structure 116 internally rather than accumulating externally at the second interface 118 and increasing the volume of the anode 104. Therefore, the anode 104 exhibits a reduced volume change during charging and discharging compared to conventional anodes.
[0046] In some embodiments, the porous structure 116 of the anode 104 has a porosity of about 60% to about 90%. In some embodiments, the anode 104 has a thickness of about 10 microns to about 100 microns in an uncharged state. Other porosities and thicknesses are used in other embodiments. In some embodiments, the porous structure 116 of the anode 104 is formed from electrospun fibers formed into a fleece-like mesh. In embodiments where the battery cell 100 is a Li-ion battery cell, the fibers comprise a Li-ion conductive ceramic ("LIC") material. Any acceptable LIC material may be used, including (i) oxide-type materials such as Li7La3Zr2O 12 (LLZO) or Li 3x La 2 / 3 −x TiO3 (LLTO), (ii) oxyphosphate type materials, such as Li 1.5 Al 0.5 Ge 1.5 P3O 12 (LAGP), (iii) sulfide materials such as Li3PS4 (LPS) or Li 10 GeP2S 12 (LGPS), (iv) a glass formulation of one of the above, or (v) a combination thereof. As discussed in more detail below, in some embodiments, at least a portion of the fibers further comprise a polymeric material and / or a conductive material.
[0047] As used herein, a "deposition biasing element" is an element having at least one of physical, chemical, and structural properties that affects the deposition of metal ions in a region of the element during charging. In some embodiments, the deposition biasing element biases the deposition of metal ions toward a region of the deposition biasing element. In some embodiments, the deposition biasing element deviates the deposition of metal ions from a region of the deposition biasing element.
[0048] In some embodiments, the deposition bias element 112 includes a seed layer 120. As used herein, a "seed layer" is a layer that contains discrete concentrations of a metallic material distributed within the layer, whereby the metallic material corresponds to the metallic ions transported during charging and discharging. For example, in this embodiment where the battery cell 100 is a Li-ion battery cell, the seed layer 120 contains discrete concentrations of Li metal corresponding to the Li ions transported within the battery cell 100. In some embodiments, the metal in the seed layer 120 exceeds the amount of metal that can migrate as ions across the separator 106 during discharge. In some embodiments, the metal in the seed layer 120 constitutes approximately 20% of the metal in the battery 100. In such an embodiment, therefore, in a fully discharged state of the battery 100, approximately 20% by weight of the total amount of metallic material in the battery remains within the seed layer.
[0049] In various embodiments, the concentration of the metal material in the seed layer 120 is in the form of clusters, nanosheets, particles, etc., or a combination thereof. The concentration of the metal material acts as a nucleation target and attractant for metal ions entering the anode 104 from the separator 106. Therefore, the seed layer 120 biases the deposition of metal ions within the anode 104 toward the first interface 114 between the first current collector 102 and the anode 104. Therefore, during charging, metal ion deposition tends to start at the first interface 114 and grow toward the second interface 118 between the anode 104 and the separator 106.
[0050] Biasing metal ion deposition to start at the first interface 114 and grow toward the second interface 118 can inhibit the formation of dendrites. As described above, dendrites may form at discontinuities or defects in the surface of the separator and cause an accelerated failure mode as the dendrites grow through the separator toward the cathode. In the battery cell 100, because metal ion deposition tends to start at the interface 114, metal ions are less likely to be deposited in the area of the second interface 118, and therefore less likely to form dendrites on the separator 106. In addition, growth from the interface 114 toward the interface 118 means that metal ion deposition tends to occur in areas of similar distances from the interface 114 until the anode 104 material at that distance is saturated with Li ions. This results in a more uniform distribution of metal ions within the anode 104, which can also inhibit the formation of dendrites by maintaining a more uniform current density.
[0051] Such biasing may also inhibit the growth of dendrites that would otherwise form despite any inhibitory factors. Specifically, biasing metal ion deposition toward the first interface causes the metal ions to tend to deposit within the porous structure 116 of the anode 104 rather than on the surface of the anode 104 at the second interface 118. Such dendrites are physically constrained by the porous structure 116 of the anode 104. In other words, dendrites formed within the porous structure 116 can only grow to contact the inner surfaces that define the internal voids of the porous structure 116 in which they are formed.
[0052] In some embodiments, the separator 106 is a solid ion conductor. Any acceptable type of solid ion conductive material can be used, including (i) polymer materials, such as block copolymers of polyethylene oxide (PEO) and styrene, polystyrene-b-poly(ethylene oxide) (SEO) doped with Li salts, or polymer materials based on other main chain materials, such as poly(vinylidene fluoride) (PVDF), PEO, poly(methyl methacrylate) (PMMA) or polyacrylonitrile (PAN), (ii) inorganic materials, such as oxides, sulfides or phosphates in the form of ceramics or glasses, or mixtures thereof, and (iii) combinations thereof. In various embodiments, the ceramic material is crystalline, amorphous or a mixture of the two. Other types of separators are used in other embodiments. In some embodiments, the separator 106 has a gel structure comprising a plasticizer and a liquid electrolyte, such as an alkyl carbonate, other solvents, etc.
[0053] In some embodiments, cathode 108 is a solid cathode comprising a cathode active material, an ionically conductive phase (i.e., a cathode electrolyte), and an electronically conductive additive. Any acceptable cathode active material may be used. In some embodiments where battery cell 100 is a Li-ion battery cell, the cathode active material is a corresponding Li-based material, such as a Li transition metal oxide in layered, spinel, or phosphate form, such as LiFePO4, LiNi x Co y Al z O2. Any acceptable cathode electrolyte can be used. In some embodiments, the cathode electrolyte is a solid material. In other embodiments, the cathode electrolyte is a combination of a liquid electrolyte material, a liquid electrolyte material and a plasticizer, or a combination of a liquid electrolyte and a solid electrolyte component. Any acceptable electronic conductive additive can be used, such as carbon black, graphite, graphene, etc., or a combination thereof. In some embodiments, the materials of the cathode active material, the cathode electrolyte, and the electronic conductive additive are selected so that the cathode 108 contains about 10% by weight of a conductive material and about 30% by weight of an ion conductive material. In some embodiments, about 80% by weight of the cathode is formed by the cathode active material. In some embodiments, the cathode 108 has a thickness of about 10 microns to about 150 microns or more.
[0054] Figure 2aAnother exemplary embodiment of a metal ion battery cell 200 according to the present disclosure is depicted. In some embodiments, the battery cell 200 is a Li-ion battery cell. The battery cell 200 includes a first current collector 202, an anode 204, a separator 206, a cathode 208, a second current collector 210, and a deposition bias element 212. The separator 206 is disposed between the anode 204 and the cathode 208. The anode 204 is disposed between the first current collector 202 and the separator 206. The cathode 208 is disposed between the separator 206 and the second current collector 210.
[0055] In some embodiments, the deposition biasing element 212 is disposed in the region of the second interface 218 between the anode 204 and the separator 206. The deposition biasing element 212, in some embodiments, includes a dendrite quenching layer 220. In some embodiments, the dendrite quenching layer 220 is formed by a coating of a dendrite quenching material that coats one or more of the anode 104 and the separator 106 within the range of the second interface 118. In some embodiments, the dendrite quenching layer 220 is formed by a dendrite quenching material dispersed within a portion of the porous structure 216 of the anode 204 adjacent to the second interface 218.
[0056] The dendrite quenching material is a material that has a relatively high tendency to form an alloy with a metal material corresponding to the metal ions transported within the battery cell 200. For example, in this embodiment where the battery cell 200 is a Li-ion battery cell, the dendrite quenching material is a material that tends to form an alloy with the Li metal, such as Sn, Ge, Au, Al, Si, In, etc. The presence of the dendrite quenching layer 220 in the region of the second interface 218 causes the metal ions in the region of the second interface 218 to tend to form an alloy with the dendrite quenching material rather than being deposited within the anode 204. Thus, metal ion deposition is biased away from the region of the second interface 218.
[0057] Additionally, the alloying propensity of the dendrite quenching material enables the dendrite quenching layer 220 to capture dendrites that may have formed within the anode 204 and that may otherwise grow toward and into the separator 206. In other words, a dendrite that forms within the anode 204 will cease to grow when the dendrite contacts and alloys with the dendrite quenching material of the dendrite quenching layer 220.
[0058] In some embodiments, the dendrite quenching layer 220 is configured to act as a dendrite growth indicator. During charging, the metal ions will tend to fill the porous structure 216 first, and therefore the metal ions will tend not to form alloys with the dendrite quenching layer 220 at first. However, as the porous structure 216 is filled and / or as dendrites grow toward the separator 206, more metal ions will tend to form alloys with the dendrite quenching layer 220 rather than being deposited in the anode 204. The transition from a majority of the transported metal ions being deposited in the anode 204 to a majority of the metal ions being alloyed with the dendrite quenching layer 220 causes a voltage fluctuation across the battery cell 200, which indicates one or more of the state of charge of the battery cell 200 and the formation of dendrites within the battery cell 200. In some embodiments, such a voltage fluctuation is about 100 mV or greater.
[0059] Figure 2b A charging system 270 for charging a battery cell 200 is depicted. A first current collector 202 and a second current collector 210 are connected to a charging device 272. The charging device 272 includes a charging element 274 configured to charge the battery cell connected to the charging device 272 and a charging manager 276. The charging manager 276 is configured to receive a signal indicative of a voltage across the first current collector 202 and the second current collector 210. In response to a voltage fluctuation exceeding a predetermined threshold, such as a fluctuation exceeding 100 mV, the charging manager 276 is further configured to interrupt charging of the battery cell 200 by the charging element 274. Using the voltage fluctuation as a trigger to stop the charging process can prevent overcharging and / or further dendrite formation.
[0060] Figure 3 Another exemplary embodiment of a metal ion battery cell 300 according to the present disclosure is depicted. The battery cell 300 includes a first current collector 302, an anode 304, a separator 306, a cathode 308, a second current collector 310, and a deposition bias element 312. The separator 306 is disposed between the anode 304 and the cathode 308. The anode 304 is disposed between the first current collector 302 and the separator 306. The cathode 308 is disposed between the separator 306 and the second current collector 310.
[0061] In some embodiments, the deposition biasing element 312 includes a coating 320 of an electronically conductive material applied to a first portion 322 of the porous structure 314 of the anode 304 adjacent to the first current collector 302 .
[0062] The second portion 324 of the porous structure 314 is not coated by the coating 322 and is purely ionically conductive, i.e., not electronically conductive. Thus, metal ion deposition is biased away from the second portion 324 and toward the first portion 322. Any acceptable electronically conductive material may be used, such as C, Si, etc. In this embodiment, the coating 322 has a nanometer-scale thickness.
[0063] In some embodiments, anode 104 is formed of a pure ionically conductive material, and the pure ionically conductive second portion 324 is from the exposed pure ionically conductive material of the anode. In some embodiments, second portion 324 of anode 304 includes another coating of ionically conductive material.
[0064] In some embodiments, the entire anode 104 is coated with an ion conductive material, and the coating 320 of the first portion 322 is disposed above the ion conductive material. In some such embodiments, the local impedance of the battery cell 300 can be used as a variable to manage the charge rate of the battery cell 300. The impedance of the anode 304 depends on at least one of the filling fraction of the metal ions in the anode 304 and the thickness of the portion of the anode 304 filled with metal ions. Therefore, in some embodiments, the battery cell charger or battery manager is configured to adjust the charge rate of the battery cell 300 with reference to the impedance of one or more of the anode 304 and the entire battery cell 300.
[0065] In some embodiments, the first portion 322 represents a majority of the anode 304 and the second portion 324 is a minority. In various embodiments, the first portion 322 and the second portion 324 represent different proportions of the anode 204. A higher proportion of the first portion 322 relative to the second portion 324 corresponds to higher dendrite control and a lower charge rate for the battery cell 300, while a lower proportion corresponds to lower dendrite control and a higher charge rate.
[0066] In some embodiments, the porous structure of the anode is formed by a fiber web produced by electrospinning. Electrospinning is a fiber production method that uses electricity to draw charged wires of materials, such as polymers, ceramics, or polymer-ceramic components, up to fiber diameters of about several hundred nanometers. A dispersion or solution of the material is pumped or sprayed through a positively charged needle injector and pulled out as a fiber onto a negatively charged substrate.
[0067] In various embodiments, fibers are formed by electrospinning from ion conductive materials such as LIC materials, polymeric materials, or combinations thereof. In some embodiments, the material particles within the fibers are of uniform size. In some embodiments, the material particles within the fibers are of various sizes. The particle size distribution within the fibers enables the fibers to be more densely packed, i.e., above the percolation threshold of the material(s) forming the fibers, which can increase the material concentration at a given volume and improve inter-particle contact within the fibers.
[0068] As discussed in more detail below, in various embodiments, the anode of the metal ion battery is formed from electrospun fibers of ion conductive ceramic material, electrospun fibers of ion conductive ceramic material and polymer material, electrospun fibers of vitrified ion conductive material, electrospun fibers of polymer material formed into a web and coated with a coating of ion conductive ceramic material. Such an anode has a low weight density relative to conventional anodes, thereby enabling high energy density in a battery cell relative to conventional battery cells.
[0069] Figure 4 An exemplary method 400 for forming an anode from electrospun fibers is depicted. At block 402, material particles are electrospun into fibers. The material particles comprise an ionically conductive material. Any acceptable ionically conductive material may be used, such as an LIC material. In some embodiments, the material particles additionally comprise particles of a polymeric material blended with particles of the ionically conductive material. In some embodiments, the polymeric material is an ionically conductive polymer, such as an ionically conductive ceramic polymer. In some embodiments using ionically conductive polymeric material particles, the polymeric material particles are treated with a solvent imbibition method (not shown) to introduce salts prior to electrospinning.
[0070] At block 404, the electrospun fibers are deposited onto a substrate to form a web. In some embodiments, the substrate is a battery component, such as a current collector or separator, and depositing the fibers includes a heating process as discussed in more detail below to bond the fibers to the substrate. In some embodiments, the substrate is configured to release the web to form a freestanding anode.
[0071] Figure 5An exemplary method 500 for forming an anode from electrospun fibers is depicted. At box 502, particles of a polymer material are electrospun into fibers, and at box 504, the fibers are deposited onto a substrate to form a web. At box 506, a coating of an ionically conductive ceramic material is applied to a portion of the fibers of the web. Any acceptable ionically conductive ceramic material, such as an LIC material, may be used. Any acceptable coating method may be used. In some embodiments, the coating is applied by dipping the web into a melt of the ionically conductive ceramic material. In some embodiments, the web is treated with a solution comprising an LIC material as a solute. In some embodiments, the entire web is coated with the coating. In some embodiments, the coated portion is less than the entire web. At box 508, a heating process is applied to the web to cure the coating onto the fibers.
[0072] Figure 6 An exemplary method 600 for forming a metal ion battery cell is depicted. At block 602, an anode having a porous structure of fibers is formed by electrospinning. At block 604, a deposition biasing element is applied to at least one of the anode and a first current collector. In some embodiments, a seed layer is applied to the first current collector. In some embodiments, the seed layer is applied to a first face of the anode. In some embodiments, a dendrite quenching layer is applied to a second face of the anode opposite the first face.
[0073] At box 606, the anode is placed between the first current collector and the separator so that the first surface of the anode forms a first interface with the first current collector, and the second surface of the anode forms a second interface with the separator. In some embodiments, the electrospinning method at box 602 includes depositing the fiber directly onto the first current collector or the separator. In some embodiments, placing the anode includes releasing the anode from the electrospinning substrate. At box 608, the first current collector, the anode, and the separator are joined together. Any acceptable joining method can be used, such as local annealing, such as focused laser heating, or low temperature sintering. At box 610, the cathode and the second current collector or an assembly including the cathode and the second current collector are joined to the side of the separator opposite to the anode so that the cathode is located between the separator and the second current collector, thereby forming a battery cell.
[0074] Although the above several embodiments relate to Li-ion and Li metal battery cells and assemblies, it should be understood that the above features and techniques can be similarly applied to other metals and metal ions. In addition, although the above several embodiments relate to a single battery cell, it is recognized that multiple battery cells can be combined in series and / or in parallel to form a battery.
[0075] It will be appreciated that variations of the above and other features and functions, or alternatives thereof, may be desirably combined into many other different systems, applications or methods. Those skilled in the art may subsequently make various currently unforeseeable or unanticipated substitutions, modifications, changes or improvements, which are also intended to be covered by the above disclosure.
Claims
1. A battery cell comprising: First Collector Fluid; Diaphragm; an anode disposed between the first current collector and the separator, the anode comprising an ion conductive material having a porous structure; and At least one deposition bias element disposed within the battery cell to bias ion deposition within the anode away from the separator during charging of the battery cell, wherein the at least one deposition bias element comprises a seed layer having a discrete concentration of a metal material corresponding to ions conducted by the ion conductive material, the seed layer disposed between a first current collector and the separator to be closer to the first current collector than to the separator, and configured to bias ion deposition within the anode toward the first current collector, wherein the discrete concentration of the metal material is in the form of clusters, nanosheets, particles, or a combination thereof, and acts as a nucleation target and attractant for metal ions entering the anode from the separator.
2. The battery cell according to claim 1, wherein the ion-conducting material is a Li-based ceramic material. 3 . The battery cell according to claim 1 , wherein the battery cell is configured so that in a fully discharged state, 20 weight % of a total amount of metal material corresponding to ions conducted by the ion conductive material remains within the seed layer.
4. The battery cell of claim 1 , wherein the at least one deposition bias element comprises a dendrite quenching layer having a material configured to form an alloy with a metal material corresponding to ions conducted by the ion conductive material, the dendrite quenching layer being disposed in an interface region between the anode and the diaphragm and configured to deflect ion deposition within the anode away from the diaphragm.
5. The battery cell of claim 1 , wherein the at least one deposition biasing element comprises an electronically conductive coating applied to a portion of the anode porous structure adjacent to the first current collector, the electronically conductive coating being configured to bias ion deposition within the anode toward the first current collector and away from the separator.
6. The battery cell according to claim 1, wherein: The anode comprises a substrate formed from fibers of a polymer material; and The ion conductive material is a coating applied to the polymer material fibers to form a porous structure.
7. The battery cell of claim 1, wherein the anode has a porosity of 60% to 90%.
8. A method of forming a battery cell, comprising: forming an anode comprising an ion-conducting material by electrospinning material particles into a web, wherein the material particles comprise the ion-conducting material, and the anode comprises the ion-conducting material having a porous structure; applying at least one deposition bias element to at least one of the anode and the first current collector; and The anode is disposed between the first current collector and the separator so that the first current collector forms a first interface with the first surface of the anode, and the second surface of the anode forms a second interface with the separator; and A first current collector and a separator are joined to the anode, wherein applying the at least one deposition biasing element includes applying a seed layer between the first current collector and the separator to be closer to the first current collector than to the separator, the seed layer comprising a discrete concentration of a metal material corresponding to ions conducted by the ion conductive material, and the seed layer is configured to bias ion deposition within the anode toward the first current collector during charging, wherein the discrete concentration of the metal material is in the form of clusters, nanosheets, particles, or a combination thereof, and acts as a nucleation target and attractant for metal ions entering the anode from the separator.
9. A method according to claim 8, wherein applying the at least one deposition bias element includes applying a dendrite quenching layer to the second side of the anode, the dendrite quenching layer comprising a material configured to form an alloy with a metal material corresponding to the ions conducted by the ion conductive material, and the dendrite quenching layer is configured to deviate ion deposition within the anode away from the diaphragm during charging.
10. The method of claim 8, wherein applying the at least one deposition biasing element comprises applying a coating of an electronically conductive material to a portion of the anode adjacent the first face, the remainder of the anode being purely ionically conductive, to bias ion deposition within the anode toward the first current collector and away from the separator during charging.
11. The method according to claim 8, further comprising: The cathode and the second current collector are joined to the side of the separator opposite the anode so that the cathode is disposed between the separator and the second current collector.
12. The method of claim 11, wherein the anode, separator and cathode are solid state such that the battery cell is a solid state battery cell.
13. The method of claim 8, wherein the ion conductive material is a Li-based ceramic material.
